Forbidden subgraph pairs for traceability of block-chains - Binlong Li; Hajo Broersma; Shenggui Zhang (Electronic Journal of Graph Theory and Applications (EJGTA), 2013)
A block-chain is a graph whose block graph is a path, i.e. it is either a $P_1$, a $P_2$, or a 2-connected graph, or a graph of connectivity 1 with exactly two end-blocks. A graph is called traceable if it contains a Hamilton path. A traceable graph is clearly a block-chain, but the reverse does not hold in general.In this paper we characterize all pairs of connected graphs $\{R,S\}$ such that every $\{R,S\}$-free block-chain is traceable.